Jan Baptist Xavery (1697-1742): A versatile garden artist (Bulletin KNOB, 2011)
Dutch garden sculpture from the 18 th century is worthy of more systematic study. Such research may offer valuable insights into the position of garden sculpture within sculpture proper and its meaning in 18 th-century garden art. Jan Baptist Xavery is regarded as one of the most important sculptors working in the Netherlands during the 18 th century. His artistic career, his versatile body of work and his influence on other artists should therefore be studied in more depth. In view of the bloom in garden art in those days Xavery's significance as a 'garden artist' should not be overlooked in such a study. Garden sculptures should not be regarded as independent objects or pure decorative elements, but must be considered within the wider context of garden history.Tragically, many garden ornaments have been removed from their natural green environment. In their new settings they sometimes acquire a new meaning, but more often than not they are not done justice as the original harmonious 'composition' has been lost. As a result, this cultural-historical heritage is often treated indifferently. The few garden sculptures that have survived all calamities and can still be admired in public places are often placed at unsuitable locations and suffer from the weather or vandalism. Many garden sculptures, often damaged, have ended up anonymously in museum depots. Although they are safe there, the dreary catacombs of museums are a far cry from the green surroundings for which they were originally intended. Garden ornaments were, after all, not made for depots but to be looked at, studied and admired by enthusiasts, preferably in green surroundings. Otherwise, they will literally disappear from collective memory. Surely, the talented Jan Baptist Xavery and his contemporaries deserve a better fate than that.